Concurrent use of Chinese herbal medicine and anticoagulants may reduce major bleeding events. - Shuo-Min Hsu; Hung-Jen Lin; Yi-Wei Kao; Te-Mao Li; Ben-Chang Shia; Sheng-Teng Huang (PLoS ONE, 2022)
Background This retrospective cohort study investigated the risk of major bleeding events during the concurrent use of Chinese herbal medicine (CHM) and anticoagulants in clinical practice. Methods A total of 4,470 patients receiving anticoagulant drugs were selected from Taiwan's National Health Insurance Research Database (NHIRD). Half (n = 2,235) were also using CHMs (CHM cohort); the other half were not (non-CHM cohort). Each cohort was matched 1:1 using the propensity score. Chi-square testing and the Student's t-test were used to examine differences between two cohorts. Cox proportional hazard regression analysis assessed the risks for major bleeding events in each cohort, as well as bleeding risks associated with specific CHM formulas and herbs. Cumulative incidence curves for major bleeding events were calculated using Kaplan-Meier analysis. Results Compared with the non-CHM cohort, the CHM cohort had a lower risk of overall bleeding events (p < 0.001) including hemorrhagic stroke (p = 0.008), gastrointestinal (GI) bleeding (p < 0.001), urogenital bleeding (p ≤ 0.001) and nasal/ear/eye bleeding (p = 0.004). Single herbs, such as Glycyrrhiza uralensis et Rhizoma, Panax notoginseng, Panax ginseng, Platycodon grandiflorum, Eucommia ulmoides Oliver and formulas, such as Shu Jing Huo Xue Tang, Shao Yao Gan Cao Tang and Ji Sheng Shen Qi Wan were associated with a lower risk of major bleeding events. Conclusion Using CHMs with anticoagulants appeared to decrease the risk of major bleeding, especially CHMs products containing Glycyrrhiza uralensis et Rhizoma, Panax notoginseng, Panax ginseng, Platycodon grandiflorum and Eucommia ulmoides Oliver. Further investigations are needed to determine whether CHM can maintain the therapeutic efficacy of anticoagulants while simultaneously reducing potential side effects.